Affective Variables and Cognitive Performances During Exercise in a Group of Adults With Type 2 Diabetes Mellitus - Guicciardi, Marco; Fadda, Daniela; Fanari, Rachele; Doneddu, Azzurra; Crisafulli, Antonio (Frontiers in Psychology, 2020)
Previous research has documented that type 2 diabetes mellitus (T2DM) is associated with cognitive impairment. Psychological variables were repeatedly investigated to understand why T2DM patients are poorly active, despite standards of medical care recommends performing aerobic and resistance exercise regularly and reducing the amount of time spent sitting. This exploratory study aims to investigate how affective variables as thoughts, feelings and individuals’ stage of exercise adoption can modulate low cognitive performances during an experimental procedure based on exercise. The Exercise Thoughts Questionnaire (ETQ: Kendzierski & Johnson, 1993), Exercise-Induced Feeling Scale (EFI: Gauvin & Rejeski, 1993), and Physical Activity Stage of Change (Marcus, Selby, Niaura & Abrams, 1992) were administered to a sample of 12 T2DM patients. The Bivalent Shape Task (BST: Esposito et al., 2013) alone (BST), with exercise (CER+BST) and with metaboreflex (PEMI+BST) was used as mental task and response time to congruent, incongruent and neutral stimuli were recorded. Concomitant cerebral oxygenation (COX) was evaluated by near-infrared spectroscopy (NIRS). As expected T2DM patients performed significantly better when the stimulus was presented into congruent trials (followed by neutral and incongruent). In the CER+BST session, T2DM patients showed longer reaction time to incongruent trials than in the PEMI+BST and BST alone sessions. Positive feelings toward exercise seem to modulate cognitive performances in a highly challenging task, only if T2DM patients were conscious to play exercise. These results could provide some insights for health intervention targeting exercise for patients with T2DM in order to enhance cognitive performances.